Left gallbladder: surgical challenge in laparoscopic cholecystectomy: a case report - Vizcaino, Jorge D. S. M.; Blas, Mauricio G.; Licona, Jennifer H. (International Journal of Research in Medical Sciences, 2025)
Left-sided gallbladder (LSGB) without situs inversus is a rare genetic anatomical abnormality, defined by the location of the gallbladder to the left side of the liver falciform and round ligaments, with incidences ranging from 0.04% to 0-7% according to various literature reports. It is gaining relevance as it becomes a surgical challenge given the potential variants of the biliary tract. This article describes the case of 55-year-old female scheduled for elective laparoscopic cholecystectomy due to 3-months-old cholelithiasis, incidentally diagnosed, in which a left gallbladder was identified. She underwent multiport laparoscopic cholecystectomy (LC), where a gallbladder implanted on the left side (in the hepatic segment III) was identified with no other apparent anomalies of the biliary tree. The procedure was performed without incident. LSGB without situs inversus, also known as “sinistraposition,” is a rare and often incidental finding that can represents a technical and surgical challenge for the general surgeon unrelated to these variants, thus increasing morbidity.